Genetic polymorphism of 8 Y-STR loci in native population of Isfahan province in central part of Iran - Nasimeh Vatandoost; Ahmad Reza Salehi; Mohammad Kazemi; Sharifeh Khosravi; Gilda Eslami; Sara Kamali; Rasoul Salehi (Taylor & Francis Group, 2017)
Background: Y-chromosome short tandem repeats (Y-STRs) are genetic markers with practical applications in human identification and population studies. Aim: Here we present the allelic and haplotype frequencies of 8 Y-STR loci most commonly used in forensic medicine in 103 unrelated native males of Isfahan province, central part of Iran. Subjects and methods: The cases were selected on the basis of strict criteria to assure pure native populations of Isfahan origin. DNA extracted from peripheral blood samples and PCR amplified for each marker. Y-specific STR loci DYS19, DYS385, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393 were included in this study. Results: The most common alleles for each locus were: DYS19, allele 12; DYS385, allele 12; DYS389I, allele 13; DYS389II, allele 29; DYS390, allele 24; DYS391, allele 10; DYS392, allele 11; and DYS393, allele 13. Gene diversity value was calculated from the allelic frequency for each locus. The average gene diversity was 0.6518. A total of 101 haplotypes were observed in eight Y-specific STR loci, the haplotype diversity was raised to 0.986. Conclusion: The results revealed that a set of eight Y-specific STR loci were able to discriminate most of the male individuals in the population studied. A search through the Y Haplotype Reference Database demonstrated 21 matched haplotypes to 160,693 haplotypes, exclusively with Eurasian-European, Eurasian, and Eurasian-Indo Iranian populations.